2012
DOI: 10.1002/jrs.4069
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy on two chalices from the Benedictine Abbey of Einsiedeln: Identification of gemstones

Abstract: The gems that adorn two golden chalices from Einsiedeln Abbey (Switzerland) crafted in 1609 and 1629 were investigated using Raman spectroscopy. The results were also compared with those obtained by other non-destructive means such as microscopy and energy-dispersive X-ray fluorescence. The chalice made in 1609 was adorned with 16 corundum (15 rubies and 1 sapphire), four garnets (two almandine and two grossular), seven quartzes (six amethysts and one citrine) and one peridot (forsterite olivine). All pearls o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…On the basis of the research carried out so far [15] and some new findings, it can be concluded that the chalice contains 456 gemstones: 24 diamonds, 93 rubies, 4 sapphires, 152 emeralds, 101 almandine garnets, 6 grossular garnets, 68 amethysts, 6 citrines, one specimen of glass and one of agate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the research carried out so far [15] and some new findings, it can be concluded that the chalice contains 456 gemstones: 24 diamonds, 93 rubies, 4 sapphires, 152 emeralds, 101 almandine garnets, 6 grossular garnets, 68 amethysts, 6 citrines, one specimen of glass and one of agate.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Raman microspectroscopy provides a nondestructive method, requiring short measurement times for the examination of gemstones, with the ability to microscopically examine either loose stones or, especially, gemstones that are mounted in various artefacts. [5,[13][14][15][16] The use of Raman spectroscopy as a method for identifying gemstones in treasures of cultural and religious heritage is very important. It was introduced as a new technique in the world of gems and gemology by Hänni and co-authors [7] in 1998.…”
Section: Introductionmentioning
confidence: 99%
“…They were grouped on the basis of their situation in the Torah shield as follows ( Fig. 1): the big yellow, blue, pink and green stones at the periphery of the shield (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), the stones in the central crown (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), the central non-translucent cabochon and small associated stones (25)(26), the stones at the crown of the right column 27-33, the red stones close to the deer head (34,35,46,47), the big stone between deer's antlers (45), the red stone in the deer's body (36), the small stones on the box for removable plates (37)(38)(39)(40)(41)(42)(43)(44), the stones at the crown of the left column (48-53) and small stones as apples in the tree crowns (54-58).…”
Section: Experimental Samplesmentioning
confidence: 99%
“…Raman spectroscopy is starting to be routinely used as a primary method for studying gemstones mounted in many historical objects in situ (Heinrich's cross dating from the late Middle Ages, [2] scepter of Faculty of Science of Charles University [3] ) or in the laboratory (golden chalices from the Einsiedeln Abbey crafted in the 17th century, [4] the Reliquary cross and Dorothy monstrance of the late Gothic period, [5] the cover of an elaborately decorated leather-bound manuscript, the Tours Gospel, 'Evangelia Quatuor' [6] ), analyses of pigments, [7][8][9][10] glass and glass products [11][12][13][14][15][16] and ceramics. [17,18] We present here the rapid and accurate in situ identification of stones using portable instruments equipped with 785-nm and 532-nm lasers, the second of them used for the identification of the red coral's pigments in resonance conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Art objects, jewels, statuettes, and religious artefacts have been often adorned by gemstones (Kiefert et al 2005). Among precious and semi-precious gemstones, minerals no harder than quartz were usually set in prehistoric artifacts (Lu et al 2005), lapis lazuli and turquoise were widely employed in Egypt (Lo Giudice et al 2009), several micro-and crypto-crystalline varieties of quartz were engraved to adorn jewels during Hellenistic Age (Barone et al 2016a), colored precious gems were used during Roman Age (Gliozzo et al 2011), red garnets, rubies, sapphires, diamonds, but also colored glass, adorned Medieval treasuries (Jehlička et al 2016;Jeršek & Kramar 2014;Karampelas et al 2012;Reiche & Lambacher 2004).…”
Section: Introductionmentioning
confidence: 99%